School repetition: analysis and reflections in an educational establishment in the commune of Valparaiso, Chile - Meriño-Montero, Ignacio (2021)
The School repetition is a multidimensional phenomenon and one of the three critical knots that education presents for the fulfillment of its universalization. With the purpose of identifying associated risk factors in an educational establishment in the commune of Valparaiso, a mixed investigation is carried out where primary and secondary sources of information are analyzed and described by means of frequency analysis, correlations, contingency tables and linear regression on a data base of 866 students, besides content analysis of semistructured interviews to six teachers. The results establish that the risk of repetition is due to socio-demographic, academic and socio-emotional factors, from which it is concluded that it is necessary to work on three components: family support, academic accompaniment and promotion of school coexistence.